Smart technologies for increasing crop water productivity - Kashyap, Suryakanta; Biswal, Bisworanjita; Ram, Hardev; Kumar, Rakesh (Indian Farming, 2020)
By reducing the amount of water required for crop production through integrating breeding/ genetic engineering and agronomic approaches along with resource management; water productivity can be increased at field and basin level is a key strategy for achieving food security and water sustainability in a world with growing demands for the both. Also greater awareness of these options among growers and policymakers can encourage more cost-effective water management strategies that can free up water for other uses. However, appropriate management strategies to increase crop water productivity will vary regionally.